Upaya Guru PPKn Dalam Mengembangkan Karakter Disiplin dan Tanggung Jawab Siswa : Studi di SMKN 1 Kuripan Lombok Barat - Gunawan, M. Hadi; Rispawati, Rispawati; Yuliatin, Yuliatin (Jurnal Ilmiah Pendidikan Indonesia, 2020)
The aim of the study was to find out the efforts of Pancasila and Citizenship Education teachers in developing the character of discipline and responsibility, and what were the supporting factors and obstacles to the teacher’s efforts in Pancasila Education and citizenship in developing the character of discipline and responsibility in SMK 1 Kuripan, West Lombok. This study uses a qualitative approach to the type of case study, data collection techniques used in this study were observation, interviews and documentation. While the data analysis technique uses data reduction, data presentation, and conclusion drawing. The results of this study indicate that the efforts of teachers of Pancasila and Citizenship Education in developing karkter discipline and responsibility are to provide exemplary and advice and enforcement of the rules. Supporting factors in development the character of discipline and responsibility are the personality of the PPKn teacher, the rules of school discipline, community participation. Meanwhile, the inhibiting factor is a broken home and community environment (student association).